Estratégias para deslocamento de cargas através de cooperação entre robôs móveis a rodas - Bragança, Jaines de Oliveira (2004)
This work deals with the control of cooperative robots, using a non linear position controller. The feedback of the control loop is carried out using a camera located over the environment where the robots actuate. After capturing an image, it is processed into a computer, which is responsible for generate the set point to the robots. It was used only a non linear position control and it was possible develop strategies for allowing the displacement of an object using two robots to push it. These strategies consist of analyzing the position and orientation of the object in order to displace it. In addition to these strategies, several tasks were developed by the robots, allowing them reaching a destination point or follow a predefined path. Also, tasks to the robots like formation in a line or side to side were implemented in this work.